ISO 9000: New Form of Protectionism or Common Language in International Trade? - Joseph A. Clougherty; Michał Grajek (European School of Management and Technology (ESMT), 2009)
International standards have the potential to both promote and hinder international trade. Yet empirical scholarship on the standards-trade relationship has been held up due to some methodological challenges: measurement problems, varied effects, and endogeneity concerns. We are able to surmount these challenges while considering the impact of one particular standard on the country-pair trade flows between 91 nations over the 1995-2005 period. To deal with these challenges, we measure the degree of standardization via the penetration of ISO 9000 in individual nations, allow ISO diffusion to manifest via multiple (quality-signaling, information/compliance-cost, and common-language) effects, and use instrumental variable and panel data techniques to overcome endogeneity concerns. We find strong evidence in support of ISO 9000 involving a common-language effect that enhances country-pair trade; yet, the evidence is more mixed with regard to the quality-signaling and information/compliance-cost effects. While we find ISO-rich nations (most notably European) to clearly benefit from the worldwide diffusion of standardization, ISO 9000 represents a de facto trade barrier for nations (e.g., the US and Mexico) lagging behind in terms of adoption.
urn:nbn:de:101:1-201106143622
Keywords: F13; L15; C51; 650; international trade; standards; technical trade barriers; ISO 9000; networks; Standardisierung; Handelshemmnisse; Protektionismus; Welt